Analisis Willingness To Pay (WTP) Sampah Rumah Tangga (Studi Kasus Perumnas Kelurahan Simpang Baru Panam Pekanbaru) - Siti Annisa; Hainim Kadir; Mardiana ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research was conducted in the Village of New Intersection Panam Pekanbaru. to find out how much WTP paid household garbage and how much garbage levy comparison of government and that there is a large field and know the elasticity of variables that influence WTP household waste in Simpang New Village Housing Panam Pekanbaru. In this study, the population is the entire group perumnas the levy garbage collected by the Department of Health Village New Intersection Panam Pekanbaru. Total population sample drawn as many as 368 and as many as 45 or 12% of the population, data analysis methods used in this research is quantitative descriptive. Simultaneous testing (F test) showed that income, education and number of family members together significantly influence WTP of household waste in the Village of New Simpang Panam. With 19.750 F count value is greater than the value of the F table 3,200. Based on the results of the calculation are known R2 value of 0.561 means that income, education and number of family members simultaneously affecting WTP of household waste by 56.10%, while 43.90% are influenced by other factors not analyzed. WTP households in Housing New Simpang village Panam larger than the existing levies and charges specified field by PERDA. The elasticity of income independent variable changes (X1) was 0.78, meaning that if income (X1) increased by 1% then willingnes To Pay (WTP) will increase by 0.78%.Keywords: WTP, Income, Education, Number of Family Members